Discovering leadership designing your success - Middlebrooks, Anthony E.; Allen, Scott J.; McNutt, Scott J.; Morrison, James L. (Los Angeles SAGE, 2020)
Discovering Leadership: Designing Your Success by Anthony Middlebrooks, Scott J. Allen, Mindy Mc Nutt, and James Morrison provides a practical, engaging foundation and easy-to-understand framework for individuals to purposefully design leadership. This action-oriented text starts with the self and helps students understand their individual strengths, styles, and skills with numerous reflection opportunities. Next, the text explores the relational aspects of leadership and best practices for motivating and inspiring followers. Finally, the text concludes by examining how leaders can transform their communities and create lasting, positive change. Practical applications and activities in each chapter help students develop their confidence, optimism, resiliency, and engagement. Regardless of your students’ background or major, they will gain the knowledge and skills they need to become thoughtful, impactful leaders.
Introduction and Foundations -- Chapter 1. A Framework for Leadership Success: Design and Your CORE -- Chapter 2. Designing Your Perceptions of Leaders and Leadership -- Chapter 3. Designing Your Leadership CapacityChapter -- 4. Your Values and Ethical Actions -- Chapter 5. Design Thinking and Brain Leading -- Chapter 6. Decision-Making -- Chapter 7. Influence, Power, and Motivation -- Chapter 8. Creativity, Problem-Solving, and Idea-Generating -- Chapter 9. Effective Practices for Leading Others to Success -- Chapter 10. Utilizing Change Processes Effectively -- Chapter 11. Culture -- Chapter 12. Leading a Team -- Chapter 13. Designing a Culture That Cares -- Chapter 14. Creating a Culture of Innovation by Jules Bruck, PhD -- Chapter 15. Entrepreneurial Leadership by Tony Middlebrooks, PhD, and Dan Freeman, PhD -- Chapter 16. Systems and Sustainability -- Glossary -- Notes -- Index
Includes bibliographical references (pages 426-449) and index.
Keywords: Leadership; Organizational behavior